Information regimes and the role of journalistic podcasts in the construction of contemporary informational narratives (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study examines the role of journalistic podcasts in constructing contemporary informational narratives, investigating their function as artifacts and devices within information regimes. Through a theoretical-reflective approach, it explores how these formats articulate narratives, influence subjectivities, and challenge power dynamics in information circulation. The analysis reveals that podcasts promote plurality in open contexts but may reinforce dominant narratives in closed regimes, contributing to critical literacy and the formation of the public sphere. The study highlights the interdisciplinary relevance for understanding contemporary informational phenomena.
Keywords: journalistic podcasts; information regimes; informational narratives